TANTANGAN BUDAYA NASIONAL DI ERA GLOBALISASI - Saiman, Saiman (Jurnal Bestari, 2009)
<!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> Cultures are potential element which is able to support national strength in a nation. Thus, they have to be managed so that they will give maximal benefits for both the people and the state. In this globalization era, state must anticipate the world actions especially on increasing science and technology. Furthermore, sometimes globalization brings negative impact. Thus, a nation should preserve its own culture. Moreover, internet is one of science and technology product which is its usage can badly affect the youth. It is because they are still hunger of information, trying to search their lives meaning and identities. Besides, they are also still going after aspirations for their future. Therefore, both the state and local government joining with another various level of institutions should protect national cultures in order not to be claimed by another country.